2022
DOI: 10.1101/2022.05.24.493356
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Weakly supervised identification of microscopic human breast cancer-related optical signatures from normal-appearing breast tissue

Abstract: With the latest advancements in optical bioimaging, rich structural and functional information is generated from biological samples, which calls for powerful computational tools to identify patterns and uncover relationships between optical characteristics and various biological conditions. Here we present a weakly supervised deep learning framework for human breast cancer-related optical signature discovery based on virtual histopathology enabled by simultaneous label-free autofluorescence multiharmonic micro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
(113 reference statements)
0
2
0
Order By: Relevance
“…Deep learning allows development of cell counters based on the image data. Studies have shown that the label-free images are suitable for automatic image analysis using deep learning networks [15][16][17]. These studies have used deep learning networks to classify malignant tissue from healthy tissue and to classify activated lymphocytes, but not for cell…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning allows development of cell counters based on the image data. Studies have shown that the label-free images are suitable for automatic image analysis using deep learning networks [15][16][17]. These studies have used deep learning networks to classify malignant tissue from healthy tissue and to classify activated lymphocytes, but not for cell…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning allows development of cell counters based on the image data. Studies have shown that the label-free images are suitable for automatic image analysis using deep learning networks [14][15][16]. These studies have used deep learning networks to classify malignant tissue from healthy tissue and to classify activated lymphocytes, but not for cell counting.…”
Section: Introductionmentioning
confidence: 99%